1988
DOI: 10.1507/endocrj1954.35.421
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Pituitary-Gonadal Function in Patients with Cushing's Syndrome.

Abstract: Basal levels of sex steroids, and the responses of LH and FSH to LH-RH were studied in twenty-five female patients with Cushing's syndrome (17 Cushing's disease and 8 adrenocortical adenoma). Only two patients had a regular menstrual cycle. Amenorrhea or oligomenorrhea had been of long duration in the other cases except for three postmenopausal patients. In patients with Cushing's disease, basal estradiol was low or below normal in 86%. Progesterone was normal in 83%, but testosterone was high in half of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 14 publications
2
13
0
1
Order By: Relevance
“…Our patients had a median age at menarche of 13 yr (range, 10 -16 yr), with only 9% giving a history of OL, an incidence in keeping with the general population (26). Previous reports of GnRH tests in women with Cushing's syndrome have variously concluded the gonadotropin response to be poor (27,28), normal (29,30), or exaggerated (31)(32)(33). All of our patients had a normal FSH reserve, and a normal or exaggerated LH response was observed in 22 of 23 patients.…”
Section: Discussionsupporting
confidence: 46%
“…Our patients had a median age at menarche of 13 yr (range, 10 -16 yr), with only 9% giving a history of OL, an incidence in keeping with the general population (26). Previous reports of GnRH tests in women with Cushing's syndrome have variously concluded the gonadotropin response to be poor (27,28), normal (29,30), or exaggerated (31)(32)(33). All of our patients had a normal FSH reserve, and a normal or exaggerated LH response was observed in 22 of 23 patients.…”
Section: Discussionsupporting
confidence: 46%
“…As is well known, this re-confirmed that hypercortisolism itself disturbs the hypothalamic-pituitary-gonadal axis in Cushing's disease [27][28][29][30][31].…”
Section: Function Of Anterior Pituitary Hormonessupporting
confidence: 69%
“…Unlike women with PCOS, many women with Cushing's syndrome have hypothalamic-pituitary suppression of gonadotropin secretion, often leading to a reduction of serum estradiol, LH, and FSH levels (279,280). An elevation of T in the blood has been reported in one half of patients with Cushing's syndrome (279,280).…”
Section: Cushing's Syndromementioning
confidence: 99%